Analysis of Syk/PECAM-1 signaling pathway in low shear stress induced atherosclerosis based on ultrasound imaging. (April 2021) - Xia, Lianghua; Zhang, Bo; Sun, Yuqing; Chen, Bingguan; Yu, Zuoren
Highlights: The spatial distribution of WSS was generated by CDFI in vivo. LSS induced inflammatory through PECAM-1/Syk signaling pathway in atherosclerosis. LSS influenced the morphology of vascular endothelial cells in vivo. Inhibition of Syk attenuated LSS-induced inflammatory response. Abstract: Background and Objective: Low shear stress (LSS) has been demonstrated to be involved in function of vascular endothelial cells. Here we tested the hypothesis that activation of Syk played an important in LSS-induced atherosclerosis via PECAM-1 signaling pathway. Methods: In vitro, primary human umbilical vein endothelial cells (HUVECs) were stimulated with parallel plate flow chamber system for 12h under normal shear stress (NSS, 15dyne/cm 2 ), LSS (5dyne/cm 2 ) and high shear stress (HSS, 25dyne/cm 2 ), respectively, followed by inflammatory response analysis. In vivo, animal models of rat fed atherogenic diet were treated with LSS stimulation by constricting abdominal aorta with a blunted needle (0.6mm in diameter). The spatial distribution of WSS of blood vessels was generated by WSS quantitative analysis software through color Doppler flow imaging with a high-frequency small animal ultrasound system. Small molecule R406, a well-demonstrated Syk inhibitor, was applied to animals as well as HUVEC cells. Results: In vivo, comparison with the control group was performed, the mean value of WSS distribution of blood vessels was lower in LSS model rat. LSS promoted expression of phosphorylated PECAM-1 (p-PECAM-1) and Syk in LSS model rats. Compared with control group, endothelial cells of the abdominal aorta become less elongated and more polygonal in LSS group, and had a slender shape in LSS with R406 group. In vitro, LSS increased the expression of p-PECAM-1, Syk and NF-κB in HUVECs. Inhibition of Syk attenuated LSS-induced inflammatory response. Conclusions: Activation of Syk resulted in LSS-induced inflammatory response via PECAM-1 signaling pathway both in vitro and in vivo . Syk might be involved in morphological changes of ECs under the influence of LSS.